Rancang Bangun Sistem Informasi Akademik Berbasis Intranet Pada MTsN Pandaan - Alde Mohammad Rilando; Arifin Puji Widodo; Anjik Sukmaaji (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2018)
Academic information system is a web-based system that can give a student's academic activity reports periodically. Information needed MTsN Pandaan is the start of recruitment of new students until graduation. The problem that occurs is summarizing data they use sheets of paper stored in the main book, which can cause data loss, when it occurred in the reporting of academic data of each period, the information generated will not actual data recap the process becomes inefficient.One of the best solutions is to build a web-based academic information system to facilitate the school in determining the information and manage the data well and up to date. This system can perform maintenance and management of data into useful information to the school about the academic activities of students in the school.The Results by using this system is to reduce errors in the input data, and manage the data well and minimize data loss.